Detection of a changepoint, a mean-shift accompanied with a trend change, in short time-series with autocorrelation. Issue 7 (9th August 2017) - Sturludottir, Erla; Gunnlaugsdottir, Helga; Nielsen, Olafur K.; Stefansson, Gunnar
ABSTRACT: In this study, a changepoint model, which can detect either a mean shift or a trend change when accounting for autocorrelation in short time-series, was investigated with simulations and a new method is proposed. The changepoint hypotheses were tested using a likelihood ratio test. The test statistic does not follow a known distribution and depends on the length of the time-series and the autocorrelation. The results imply that it is not possible to detect autocorrelation and that the estimate of the autocorrelation parameter is biased. It is therefore recommended to use critical values from the empirical distribution for a fixed autocorrelation.